Religious Psychotherapy for Depressive and Anxiety Disorder: A Systematic Review - Rihadatul Aisy Mardhiyah (Journal of Comparative Study of Religions (JCSR), 2022)
This study aims to determine the effect of religious accommodation on psychotherapy in anxiety and depression disorders. This review systematically examines clinical trials of the integration of religion and psychotherapy for treating patients with depression or anxiety. The results of the studies review shown that psychotherapy using religious alternatives effective for treating depression and anxiety as other types of psychotherapy.  Integrating religion into psychotherapy has shown a variety of results. But some studies shown that religious can support mental illness, and prayer can be alternative to meditation in psychotherapy. Religion and psychotherapy can affect anxiety, depression, suicide, and bipolar in the psychotherapy practice. Religion and psychotherapy can build self-control in people, and religion and psychotherapy can drive people to their well-being. But in the studies shown that in the practice of psychotherapy, the use of religion and spirituality as alternatives to meditation is still separated. This results in many variations of results in studies of religion and spirituality in psychotherapy practice.